(untitled) (CIPEEX, 2025)
Given the constant transformations and innovations in the field of medicine, driven by the increasing integration with technological development, it is essential for healthcare professionals to develop a deep and comprehensive understanding of hospital management systems. In this context, the research project linked to the Saúde Salva Vidas (SSV) program emerges as a highly promising initiative, with the goal of offering doctors an optimized, intuitive, and efficient interface for the use of these platforms.This interface aims to enhance the organization of forms, medication control, and other essential processes, ensuring greater agility and accuracy in patient care. Furthermore, the project not only seeks to improve the efficiency of daily procedures in healthcare units but also to reduce the administrative workload of professionals, allowing them to focus more on direct patient care. With the implementation of SSV, a smoother integration between various hospital sectors is expected, promoting more efficient communication between medical and administrative teams, resulting in faster, safer, and more personalized care.Since patient care can be a time-consuming and detailed task, the project team has developed a proposal involving direct interaction with doctors and other healthcare professionals through questionnaires and meetings to identify practical needs and develop plans to optimize the care process, demonstrating speed and practicality. The expected result is the enhancement of the relationship between professionals and patients, as well as the automation of tasks in clinics and hospitals, leading to a qualitative leap in healthcare management.Thus, the SSV project is expected to meet the needs of healthcare professionals, with its accessibility and efficiency, significantly improving the quality of medical care and advancing the field of medicine as a whole.